Influence of fertilization and row spacing on seed yield and quality of Lathyrus sativus L. - Nelly Lili Fînaru; Adrian Ilie Nazare; Tudor George Aostăcioaei; Carmen Simona Ghițău; Teodor Robu (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
Pulses provide, along with other species, a rich source of nutrients needed both for human food and animal feed. These include Lathyrus sativus L, a grain legume that is less cultivated worldwide, especially in Europe, but of interest because of its ecological plasticity such as tolerance to drought, waterlogging, salinity, etc.